The Conveyance of the Japanese Atmosphere to Visitors as a Performance at Marugame Udon, Solo Paragon Lifestyle Mall - Majid, Ainun; Suastiwi, Suastiwi; Simatupang, Gabriel Roosmargo Lono Lastoro (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
Marugame Udon is a Japanese fast-food restaurant chain with many branches in Indonesia. This study examines the conveyance of the Japanese atmosphere to visitors as a performance. Interior research based on performance theory has not been widely conducted. This study aims to determine the performative influence of Marugame Udon’s interior on visitors by exploring Richard Schechner’s performance aspects (action, interaction, relationship). This study uses a qualitative approach with a case study method to deeply explore data from visitors and interior elements. The data collection techniques used are observation, in-depth interviews, literature study, and company profile reading. Data analysis is done by reduction, presentation, and drawing conclusions and recommendations. The findings of this study are: (1) the “action” exploration finds that the interior display is a manifestation of Marugame Udon’s identity as a Japanese restaurant chain and its commitment to introducing Japanese culture, especially Sanuki; (2) the “interaction” exploration finds that the presence of interior elements is a mutually dependent system in displaying the atmosphere (Japanese), and visitors interact most with noren and the theater kitchen; (3) the “relationship” exploration reveals that Marugame Udon does not only act as a restaurant providing food and drinks but also as a stimulating agent that influences visitors’ perceptions and evokes their memories and desires related to Japanese culture. These three findings indicate that Marugame Udon’s interior is a static performative ecosystem that can interact and form relationships with visitors.